Microbially induced pseudotraces from a Pantanal soda lake, Brazil : Alternative interpretations for Ediacaran simple trails and their limits - Veríssimo Warren, Lucas (2020)
Despite the absence of metazoans, structures resembling animal traces are common in a soda lake from the western Brazil Pantanal wetland. Pantanal soda lakes are ecologically extreme environments that preclude complex life, allowing extremophiles to flourish. Direct observation indicates that these structures are pseudotraces, representing groove marks that result from the interaction of wave-transported floating rafts of epibenthic microbial mat fragments with the substrate. Variations in wind/wave direction and intensity result in marks of different size and morphology. The most common pseudotraces are simple and slightly curved, narrow grooves (type 1), whereas others are straight and present raised lateral ridges (type 2). Both are V-shaped in cross section. Type 3 comprises long, sinuous, shallow grooves, displaying internal crescentic laminated infill and U-shaped cross section. The similarity of these pseudotraces to Ediacaran structures usually interpreted as animal trace fossils suggests that care should be exercised in their analysis. A set of criteria is proposed to differentiate microbially induced pseudotraces from trace fossils. Analysis of Ediacaran structures needs to be performed on a case-by-case basis, taking into account morphology, orientation, and preservation style of the structure, sedimentary environment, and presence or absence of microbial mats.